A water-soluble turn-on fluorescent probe for rapid discrimination and imaging of Cys/Hcy and GSH in cells and zebrafish through different fluorescent channels. (March 2022) - Wang, Xiao-Bo; Li, Hui-Jing; Liu, Chang; Lu, Wen-Yu; Lu, Xuhao; Wu, Yan-Chao
Abstract: Biothiols are a class of amino acids containing mercaptan (thiol, SH) groups that have similar structures but play different roles in physiological activities, making it important to effectively distinguish them. Here, a simple water-soluble probe, PMCI, was developed for the first time to rapidly discriminate Cys/Hcy and GSH by dual excitation and emission wavelengths. The introduction of an N –Me pyridinium salt thioether group into the fluorophore structure not only makes the probe highly water-soluble, but also serves as a potential reactive site for biothiols, which together with an aldehyde group allows the simultaneous differential detection of Cys/Hcy and GSH. The probe itself has no background fluorescence due to the intramolecular photoinduced electron transfer (PET) effect. After reaction with biothiols, the probe solution showed different strong fluorescent signals (green: Cys and Hcy, red: GSH). It can respond quickly to biothiols (Cys: 190 s; Hcy: 155 s; GSH: 80 s) with high selectivity and low detection limit. Moreover, the probe has been successfully used for the rapid discrimination imaging of endogenous and exogenous biothiols in cells and zebrafish through dual fluorescent channels. Graphical abstract: Image 1 Highlights: A coumarin-derived water-soluble turn-on fluorescent probe PMCI was developed. The probe can rapidly discriminate Cys/Hcy and GSH (Cys: 190 s; Hcy: 155 s; GSH: 80 s) with high selectivity and sensitivity. The probe can be used to distinguish and image Cys/Hcy and GSH in cells and zebrafish by dual fluorescence signals.